ANALYSIS OF LIVING LAW INTEGRATION IN INDONESIAN CRIMINAL LAW REFORM - Dwi Kurniawan, Itok; Patria Setyawan, Vincentius (Berajah Journal, 2024)
The principle of formal legality promoted by the WvS-NI translation of the Indonesian Criminal Code (Old Criminal Code) has laid down statutory regulations (written law) as the only basis for implementing criminal law provisions. The principle of formal legality has closed the existence of the living law of Indonesian society which has existed since the Indonesian state was still in the form of kingdoms. The purpose of writing this article is to analyze the integration of living law into criminal law in updating the principle of legality, which was originally only a formal legality principle, but now also includes a material legality principle. This article was written using a normative legal research method with a conceptual approach. The result of this research is that the integration of living law as a source of criminal law to implement criminal law provisions is a positive step to provide space for the application of the original laws of the Indonesian nation. However, in its implementation, comprehensive regulations are needed, especially regarding the institutionalization of living law because its nature is local, while criminal law is national. Apart from that, there is also a need for a common perception regarding the measures of justice so as to create legal certainty regarding the application of living law in criminal law.